Using neutrons, X-rays and nuclear magnetism to determine the role of transition metal oxide inclusions on both glass structure and stability in automotive glass enamels. Issue 20 (9th May 2018) - Bowron, Daniel T.; Booth, Jonathan; Barrow, Nathan S.; Sutton, Patricia; Johnson, Simon R.
Abstract : Low levels of transition metal oxides in alkali borosilicate glass systems can drastically influence crystallisation and phase separation properties. Abstract : Low levels of transition metal oxides in alkali borosilicate glass systems can drastically influence crystallisation and phase separation properties. We investigated the non-monotonic effect of manganese doping on suppressing crystallisation, and the influence on optical properties by iron oxide doping, in terms of local atomic structure. Structural models based on empirical potential structure refinement were generated from neutron and X-ray scattering data, and compared against multinuclear solid-state NMR. This revealed that a 2.5% manganese doping had a disruptive effect on the entire glass network, supressing crystallisation of an undesired bismuth silicate phase, and that iron species preferentially locate near borate tetrahedra. Preventing phase separation and controlling crystallisation behaviour of glass are critical to the ultimate properties of automotive glass enamels.